Optimised performance of a thermally resistive PV glazing technology: An experimental validation. (November 2019) - Cuce, Erdem; Cuce, Pinar Mert
Abstract: Thermally resistive PV glazing (TRPVG), which is a recently developed technology for low/zero carbon buildings, is in the centre of interest worldwide as a consequence of multifunctional benefits of this novel product such as remarkably better thermal insulation performance compared to conventional PV and other fenestration technologies in market, clean energy generation, self-cleaning, sound insulation, UV and IR absorption, etc. In this study, thermal insulation performance of TRPVG is numerically optimised through a well-known CFD software ANSYS FLUENT. Optimisation is based on determining the optimum inert gas (argon) thickness ( τ ) behind the amorphous silicon (a-Si) PV module which yields to minimum overall heat transfer coefficient (U-value) for the entire structure. For a typical case ( τ = 16 mm), CFD results are compared with the experimental data derived from the standardised co-heating tests, and a good accordance is achieved. CFD results are also compared with the findings of thermal resistance approach, which assumes heat conduction takes place in the inert gas medium only. The results reveal that natural convection effects become notable for the values of τ over 10 mm. In other words, τ stands as a parameter that needs to be optimised for its values greater than 10 mm. For the typical TRPVG sample with τ = 16 mm, the overall U-value from the CFD research is determined to be 1.19 W/m 2 K, which is in good agreement with the experimental data. The optimised value of τ for the TRPVG structure introduced is determined to be 20 mm, which guarantees the minimum total heat transfer rate (Q) across the glazing and maximum temperature difference between internal and external glazing surfaces. Highlights: Argon behaves as a thermal insulator until τ = 20 mm. The U-values from CFD and hot box tests are 1.192 and 1.135 W/m 2 K, respectively. Thermal resistance approach is not valid after τ = 12 mm. PVC-U edge seals eliminate the thermal bridging effects due to metallic dividers. TRPVG-Ar16 is ideal for energy-efficient retrofitting of existing buildings.